Neuromuscular adaptations and sensorimotor integration following a unilateral transfemoral amputation - Claret, Claudia Ramos; Herget, Georg W.; Kouba, Lukas; Wiest, Daniel; Adler, Jochen; von Tscharner, Vinzenz; Stieglitz, Thomas; Pasluosta, Cristian (Journal of neuroengineering and rehabilitation, 2019)
Background Following an amputation, the human postural control system develops neuromuscular adaptations to regain an effective postural control. We investigated the compensatory mechanisms behind these adaptations and how sensorimotor integration is affected after a lower-limb transfemoral amputation. Methods Center of pressure (CoP) data of 12 unilateral transfemoral amputees and 12 age-matched able-bodied subjects were recorded during quiet standing with eyes open (EO) and closed (EC). CoP adjustments under each leg were recorded to study their contribution to posture control. The spatial structure of the CoP displacements was characterized by measuring the mean distance, the mean velocity of the CoP adjustments, and the sway area. The Entropic Half-Life (EnHL) quantifies the temporal structure of the CoP adjustments and was used to infer disrupted sensory feedback loops in amputees. We expanded the analysis with measures of weight-bearing imbalance and asymmetry, and with two standardized balance assessments, the Berg Balance Scale (BBS) and Timed Up-and-Go (TUG). Results There was no difference in the EnHL values of amputees and controls when combining the contributions of both limbs ( p = 0.754). However, amputees presented significant differences between the EnHL values of the intact and prosthetic limb ( p <  0.001). Suppressing vision reduced the EnHL values of the intact ( p = 0.001) and both legs ( p = 0.028), but not in controls. Vision feedback in amputees also had a significant effect (increase) on the mean CoP distance ( p <  0.001), CoP velocity ( p <  0.001) and sway area ( p = 0.007). Amputees presented an asymmetrical stance. The EnHL values of the intact limb in amputees were positively correlated to the BBS scores (EO: ρ = 0.43, EC: ρ = 0.44) and negatively correlated to the TUG times (EO: ρ = − 0.59, EC: ρ = − 0.69). Conclusion These results suggest that besides the asymmetry in load distribution, there exist neuromuscular adaptations after an amputation, possibly related to the loss of sensory feedback and an altered sensorimotor integration. The EnHL values suggest that the somatosensory system predominates in the control of the intact leg. Further, suppressing the visual system caused instability in amputees, but had a minimal impact on the CoP dynamics of controls. These findings points toward the importance of providing somatosensory feedback in lower-limb prosthesis to reestablish a normal postural control. Trial registration DRKS00015254 , registered on September 20th, 2018.